Ultrastructural evidence of mitochondrial pathology in hippocampal reactive astrocytes of β-amyloidosis Alzheimer’s transgenic mice - López Oliva, Elba; Trujillo-Estrada, Laura Isabel; Sánchez-Mejías, Elisabeth; Mejías-Ortega, Marina; Fernández-Valenzuela, Juan José; Gómez-Arboledas, Ángela; Dávila-Cansino, José Carlos; Vitorica Ferrández, Javier; Gutiérrez-Pérez, Antonia (Cold Spring Harbor Laboratory, 2022)
Astrocytes, the most abundant non-neuronal cell type in the CNS, play essential roles in brain homeostasis and neuroprotection, including metabolic support, synaptic plasticity, cerebral blood flow and immunity. Many of these activities are highly energy demanding and require large energy input from efficient mitochondria. During the pathogenic process of Alzheimer’s disease (AD), amyloid-beta and phospho-tau pathologies have a detrimental effect on neurons and glial cells, also impairing mitochondrial function. This could negatively affect neuronal stability, compromising ATP production and energy metabolism, leading to a deleterious effect promoting neurodegeneration. Though the mitochondrial dysfunction is thought to be an early event in the pathogenesis of AD, the majority of studies have focused on neurons, and little is known about their functional characteristics in astrocytes. We aim to analyze mitochondrial subcellular features of rective astrocytes in APP/PS1 mice hippocampus by transmission electron microscopy and image analysis. Reactive astrocytes cluster around amyloid plaques and display marked morphological changes. Our results show mitochondrial structural alterations including mitochondrial cristae loss, broken double membrane structure and fragmentation. In addition, an increase in both number and size of mitochondria in this transgenic model compared to age-matched WT mice, was found. Since mitochondrial morphology is directly related to mitochondrial fusion/fission, the ultrastructural pathology of astrocytic mitochondria in this amyloidogenic model suggests dynamics abnormalities in these organelles that might lead to astroglial functional deficits compromising neuronal survival. Deciphering the mechanisms underlying this pathological phenomenon might help for the development of therapeutic interventions targeted to protect/improve astrocytic mitochondrial function and, in consequense, enhace their neuroprotective support to neurons in AD.
Keywords: Astrocitos; Alzheimer, Enfermedad de; Mitocondrias; Astrocyte; Neuroinflammation; Mitochondria